Pengembangan Blog Sebagai Media Pembelajaran Matematika - Nugroho, Aji Arif; Putra, Rizki Wahyu Yunian; Putra, Fredi Ganda; Syazali, Muhamad (Al-Jabar: Jurnal Pendidikan Matematika, 2017)
This study aims to test the feasibility of media-based learning Blog in learning mathematics on trigonometric subjects. This development research uses 8 stages from 10 stages of borg and gall method that are potential and problem, data collection, product design, product validation, product revision, product test, product revision and mass production. Learning media blogs are developed with the help of adobe flash which aims to provide some animation. This research was conducted in SMA Negeri 1 Batanghari class X students. The assessment instrument used was questionnaire of feasibility test by media expert, Expert of Material, and Questionnaire of student response. The results of the research are: 1) Based on the validation of material expert judgments obtained an average score of 4.65 is located in the category of "Very Good". Validation of expert media judgment obtained an average score of 4.35 in the category of "Very Good". Validation of the linguist's assessment obtained an average score of 4.5 that is in the category of "Very Good". In addition, the results of small-scale test responses of learners obtained a score of 4.23 on the criteria of "Very Good", and while on a large-scale test the learners' response to get an average score of 4, 19 is on the criteria of "Good". Thus it can be concluded learning media berbantuan blog is in good category and can be used in learning, especially on Trigonometry material.